Corporate Indebtedness and Low Productivity Growth of Italian Firms - Anderson, Gareth (IMF Working Papers; Working Paper, 2018)
Productivity growth in Italy has been persistently anemic and has lagged that of the euro area over the period 1999-2015, while the indebtedness of its corporate sector has increased. Using the ORBIS firm-level database, this paper studies the long-term impact of persistent corporate-debt accumulation on the productivity growth of Italian firms and investigates whether total factor productivity growth varies with the level of corporate indebtedness. We employ a novel estimation technique proposed by Chudik, Mohaddes, Pesaran, and Raissi (2017) to account for dynamics, bi-directional feedback effects, cross-firm heterogeneity, and cross-sectional dependence arising from unobserved common factors (for example, oil price shocks, labor and product market frictions, and stance of global financial cycle). Filtering out the effects of unobserved common factors and controlling for firmspecific characteristics, we find significant negative effects of persistent corporate debt build-up on total factor productivity growth, and weak evidence of a threshold level of corporate debt, beyond which productivity growth drops off significantly. Our results have strong policy implications, for example the design of the tax system should discourage persistent corporate debt accumulation, and effective and timely frameworks to reduce corporate debt overhangs are essential.